Geoheritage 1. Geodiversity: A New Paradigm for Valuing and Conserving Geoheritage - Gray, Murray (Geoscience Canada, 2008)
SUMMARY The term ‘geodiversity’ was first used in 1993 as the geological equivalent of biodiversity. It has gained in international acceptance and usage in recent years, and now warrants the status of a geological paradigm. Geodiversity forms the basis for the selection of geoconservation sites, which should be chosen to represent the geodiversity of a country, province or region. The objectives and methods of geoconservation vary, depending on which element of geodiversity is being considered. For example, the formal protection of static geological and geomorphological sites needs to be supported by legislation, but geoconservation of landscapes, soils and physical processes in the wider landscape is best promoted through both, policy and partnership approaches.